Study of potential use of ground-based radioelectronic equipment radiation reflected from orbital space object - Ахмедов, Д. Ш.; Еремин, Д. И.; Кемешева, Д. Г.; Альников, Д. В. (Journal of Mathematics, Mechanics and Computer Science, 2017)
In article the evaluation of specifications of reflected radiation of electronic means is produced. Outline of construction of the system of radio communication with using low-orbit space vehicles is presented. The equation of power of the radiator dependent from radar cross-section of space objects, configurations, material of which the objects is made, lengths of the wave of radio-electronic facilities, polarization, and the direction of radiation is presented. Required power of the signal of the transmitter is determined with the aid of application Radar Equation Calculator in multi-paradigm numerical computing environment Matlab, at calculation we were used of given existing systems. On received results of calculations, there is opportunity to receive a useful signal re-scattered from the group of space objects on low Earth-orbital orbit. In article, the analyzer application of the signal Radar Waveform Analyzer in environment Matlab is presented, with the aid of which possibly to simulate and to be discharged of minimum and maximum range; to visualize real and imaginary parts, magnitude and phase schedules, signal autocorrelation and spectral analysis of the signal.